A Review on Process Parameters and their effects on Dissimilar Friction Stir Welding of Aluminium and Steel Alloys - Chitturi, V. (Institute of Physics Publishing, 2019)
Friction Stir Welding (FSW) presents numerous advantages over conventional fusion welding techniques such as eliminating the need for a shielding gas, requiring less energy per weld, and the lack of a flame or arc making it safer in the work place. Another advantage of FSW is its ability to join materials that are extremely difficult, or impossible to weld with conventional fusion techniques. The growing need for dissimilar welding relates to joining aluminium and steel base metals. Individually, both metals are utilized extensively in the automotive and aerospace industries due to various advantages respectively, including lightweight, high specific strength, and recyclability. Like conventional welding methods, the intermetallic compound formation represents the main problem issue in FSW. Heat cycle has a significant effect on Intermetallic Compounds thickening phase transformation and the elimination of the amorphous phase. The hybrid techniques utilized in FSW for Al-to-steel joints reveal high joint strength in conjunction with high costs of setup and equipment. These techniques modify the steel flow around the rotated pin by acting as an assisted heat source. Process parameters play the most important role in defining the quality of the weld to withstand. In this paper we are going to discuss the effect of different parameters on Dissimilar FSW. Â© 2019 Published under licence by IOP Publishing Ltd.